Lowpass Filter with Hilbert Curve Ring and Sierpinski Carpet DGS - Dian Widi Astuti; Intan Wahyuni; Muslim Muslim; Mudrik Alaydrus (Universitas Ahmad Dahlan, 2018)
Good performance and compact size are the paramaters which are vital when desiging a filter. One of the creteria of good performance is selectivity. This research, conducted by Hilbert Curve Ring and Siepinski Carpet, is used as defected ground structure to overcome filter selectivity. By using three cascadeds Hilbert Curve Ring defected ground structure cells and three steps Sierpinski carpet, a lowpass filter is designed and fabricated. The measurement result for lowpass filterwith Hilbert Curve Ring defected ground structure has sharper selectivity with the cut off frequency at 2.173 GHz and the insertion loss value is 2.135 dB. While the measurement result for three steps Sierpinski carpet has the cut off frequency at 1.728 GHz and the insertion loss value is 0.682 dB.